PENGARUH PENAMBAHAN PROBIOTIK DYS SYNBIOTIC DENGAN DOSIS YANG BERBEDA PADA PAKAN BUATAN TERHADAP PERTUMBUHAN UDANG VANNAME (Lithopenaus Vannamei) - Edho Pawenang; M. Bahrus Syakirin; Benny Diah Madusari (LPPM Universitas Pekalongan, 2022)
This research was conducted on 14 December - 14 January 2021 at the Brackish Water Cultivation Laboratory, Faculty of Fisheries, Pekalongan University. The purpose of this study was to determine the best dose for absolute biomass growth, and survival of vannamei shrimp (Lithopenaus vannamei). This study used a completely randomized design (CRD) with 4 treatments and 3 replications. The treatments used were: A (feeding without probiotics), B (giving dys synbiotic probiotics at a dose of 10 ml / kg of feed), C (giving dys synbiotic probiotics at a dose of 15 ml / kg of feed), D (giving dys synbiotic probiotics with dose of 20 ml / kg of feed). The results showed that the highest average growth was obtained in treatment D with a dose of dys synbiotic probiotic 20 ml / kg of feed, the increase in biomass reached 2.83 gr. Meanwhile, the lowest growth was obtained in treatment A without probiotics resulting in an average growth of 1.55 g / kg of feed. The results of the analysis of variance on the growth of vannamei shrimp biomass were F count greater than F table 1% and 5%. The range of water temperature during the study was between 28-29OC, water pH ranged from 7.7-7.8 and salinity ranged from 20 ppt. Water quality conditions during the study were in the proper range for vannamei shrimp life